Homonym in Meriaq Meriku Dialect in Kawo Central Lombok - Bidarita Widiati (Universitas Pendidikan Mandalika, 2020)
This research is aimed at finding and describing the Homonym words in Meriaq Meriku Dialect in Kawo Central Lombok. Ambiguity may occur in interpreting the meaning in the form of homonymy because Homonym word has more than one meaning. The method which is applied here is a descriptive qualitative approach, by finding some homonym word and describing them. There are ten words in Meriaq Meriku Dialect which categorized as homonym. They are mangan [mangΛn], gigi [gIgI] , genit [gƐnit] , siku [sikƲ], paku [pΛkƲ], poto [p0t0] , sangkok [saȠgk0k], daun [dawƲn] , semen [semEn], and bau [bΛƲ].